2019
DOI: 10.1029/2019ja026851
|View full text |Cite
|
Sign up to set email alerts
|

Color Ratios of Subauroral (STEVE) Arcs

Abstract: Photos of a spectacular optical phenomenon, nicknamed STEVE, show finely structured, purple‐colored, east‐west arcs spanning the sky. These purple Sub‐auroral Arc Emissions are associated with Sub‐Auroral Ion Drifts, often accompanied by separate green arcs frequently displaying magnetic field aligned rays suggesting charge particle excitation. Both types of these arcs and polar auroras appear in some photos. Splitting the images into red, green, and blue channels allowed comparison of color ratios of the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 17 publications
4
20
0
Order By: Relevance
“…The spectrum of the green picket fence arc measured by Gillies et al () has an intense component of the OI 557.7 nm green line with minimal contribution by the N 2 + first negative band, which is a major spectral component in most auroras. This finding was corroborated with DSLR color photography, which showed that the green to blue ratios in picket fence images were much larger than in auroras (Mende & Turner, ). The lack of the N 2 + first negative emission could imply the lack of atmospheric N 2 in the regions where the picket fence arcs are produced.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The spectrum of the green picket fence arc measured by Gillies et al () has an intense component of the OI 557.7 nm green line with minimal contribution by the N 2 + first negative band, which is a major spectral component in most auroras. This finding was corroborated with DSLR color photography, which showed that the green to blue ratios in picket fence images were much larger than in auroras (Mende & Turner, ). The lack of the N 2 + first negative emission could imply the lack of atmospheric N 2 in the regions where the picket fence arcs are produced.…”
Section: Discussionsupporting
confidence: 57%
“…We discuss the implications of this finding and show that it is inconsistent with the picket fence being caused by precipitation from the magnetosphere. Second, we revisit the image analyzed by Mende and Turner () to show that the color ratios in photographs of the green picket fence structures are consistent with the Gillies et al, spectrum and that they are almost purely green with very little other colors in the visible spectral range compared to normal auroras. The presence of the low excitation energy emissions such as the OI green 557.7 line and the N 2 first positive and the lack of high excitation energy emissions commonly seen in aurora (e.g., N 2 + 427.8 nm) would be strong evidence for the presence of superthermal electrons and against the energetic particle precipitation hypothesis for the green picket fence structures.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…The STEVE AGC may also partly explain the result in Mende and Turner (2019). Since the beginning of the STEVE research, there has been curiosity about the similarity between STEVE and SAR.…”
Section: Summary and Discussionmentioning
confidence: 99%